2021
DOI: 10.1101/2021.02.04.21251140
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Longitudinal serology in SARS-CoV-2 infected individuals in India – a prospective cohort study

Abstract: Clinical and epidemiological characteristics of SARS-CoV-2 infection are now widely available, but there are little data on longitudinal serology in large cohorts, particularly from low-and middle-income countries. We established an ongoing prospective cohort of 3840 SARS-CoV-2 RT-PCR positive individuals in the Delhi-National Capital Region of India, to document clinical and immunological characteristics during illness and convalescence. The IgG responses to the receptor-binding domain (RBD) and nucleocapsid… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 25 publications
(25 reference statements)
1
8
0
Order By: Relevance
“…In this study nearly one in four participants with a past history of COVID-19 disease were seronegative, a finding consistent with previous rounds where antibodies to COVID-19 were lacking in a substantial proportion of the participants [2]. These findings could be attributed to the growing evidence suggestive of the waning of IgG antibodies especially during asymptomatic and mild illness, although the risk of Covid-19 reinfection in previously infected patients remains low [9,10].…”
Section: Discussionsupporting
confidence: 87%
“…In this study nearly one in four participants with a past history of COVID-19 disease were seronegative, a finding consistent with previous rounds where antibodies to COVID-19 were lacking in a substantial proportion of the participants [2]. These findings could be attributed to the growing evidence suggestive of the waning of IgG antibodies especially during asymptomatic and mild illness, although the risk of Covid-19 reinfection in previously infected patients remains low [9,10].…”
Section: Discussionsupporting
confidence: 87%
“…The proportion of adults who did not seroconvert were similar to that observed in our study. Other studies in adults have reported variable seroconversion rates between 5 and 25% 30,[37][38][39] . Viral load was similar between children and adults in our cohort, which does not explain why fewer children seroconverted compared with adults.…”
Section: Discussionmentioning
confidence: 89%
“…Results: Among 108 SARS-CoV-2 PCR-positive participants, 57 were children (median age: 4, IQR 2-10) and 51 were adults (median age: 37, IQR [34][35][36][37][38][39][40][41][42][43][44][45]. Using three established serological assays, a lower proportion of children seroconverted compared with adults [20/54 (37.0%) vs 32/42 (76.2%); (p<0.001)].…”
Section: Main Outcomes and Measures: Sars-cov-2 Antibody And Cellular Responses In Children Andmentioning
confidence: 99%
“…In this study, nearly one in four participants with a history of COVID-19 disease were seronegative, a finding consistent with previous serosurveys where antibodies to COVID-19 were lacking in a substantial proportion of the participants [ 8 ]. These findings could be attributed to the growing evidence, suggestive of the waning of IgG antibodies, especially during asymptomatic and mild illness, although the risk of COVID-19 reinfection in previously infected patients remains low [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%